Intra-articular delivery of extracellular vesicles secreted by chondrogenic progenitor cells from MRL/MpJ superhealer mice enhances articular cartilage repair in a mouse injury model - Wang, Rikang (Stem Cell Res Ther, 2020)
BACKGROUND: Chondrogenic progenitor cells (CPCs) have high self-renewal capacity and chondrogenic potential. Intra-articular delivery of purified mesenchymal stem cells (MSCs) from MRL/MpJ “superhealer” mice increased bone volume during repair and prevents post-traumatic arthritis. Recently, although extracellular vesicles released from MSCs have been used widely for treating OA, the application of extracellular vesicles secreted by CPCs from MRL/MpJ mice in OA therapy has never been reported. In this study, we evaluated the effects of extracellular vesicles secreted by CPCs from control CBA (CBA-EVs) and MRL/MpJ mice (MRL-EVs) on proliferation and migration of murine chondrocytes. We also determined here if weekly intra-articular injections of CBA-EVs and MRL-EVs would repair and regenerate surgically induced model in mice. METHODS: CPC surface markers were detected by flow cytometry. CBA-EVs and MRL-EVs were isolated using an ultrafiltration method. Nanoparticle tracking analysis, transmission electron microscopy, and western blots were used to identify extracellular vesicles. CBA-EVs and MRL-EVs were injected intra-articularly in a mouse model of surgical destabilization of the medial meniscus (DMM)-induced OA, and histological and immunohistochemistry analyses were used to assess the efficacy of exosome injections. We used miRNA-seq analysis to analyze the expression profiles of exosomal miRNAs derived from CBA-EVs as well as MRL-EVs. Cell-counting and scratch assays were used to evaluate the effects of CBA-EVs and MRL-EVs on proliferation and migration of murine chondrocytes, respectively. Meanwhile, a specific RNA inhibitor assesses the roles of the candidate miRNAs in CPC-EV-induced regulation of function of chondrocytes. RESULTS: Both CBA-EVs and MRL-EVs stimulated chondrocyte proliferation and migration, but MRL-EVs exerted a stronger effect than CBA-EVs. The similar result was also observed in in vivo study, which indicated that injecting either CBA-EVs or MRL-EVs attenuated OA, but MRL-EVs showed a superior therapeutic effect in comparison with CBA-EVs. The results of bioinformatics analyses revealed that the differentially expressed exosomal miRNAs participated in multiple biological processes. We identified 80 significantly upregulated and 100 downregulated miRNAs. Moreover, we found that the top 20 differentially expressed exosomal miRNAs connected OA repair to processes such as AMPK signaling, regulation of autophagy, and insulin signaling. Notably, miRNA 221-3p were highly enriched in MRL-Exos and treatment with miR 221-3p inhibitor markedly decreased chondrocyte proliferation and migration induced by CBA-EVs or MRL-EVs in vitro. CONCLUSIONS: This is the first study to demonstrate MRL-EVs had a greater therapeutic effect on the treatment of OA than CBA-EVs. This study will hopefully provide new insight into the pathogenesis, prevention, and treatment of OA.